In conversation W.V. Quine. (Philosophy International, 1994)
In this program, Prof. Quine is questioned about his views on the major topics in philosophy of mind. His linguistic behaviorism is examined and compared with programs in linguistics and neuroscience. It concludes with Quine's views of mental causation and consciousness.